Economic Survey of Latin America and the Caribbean 2023 - Economic Commission for Latin America; the Caribbean (United Nations, 2023)
The 2023 edition of the Economic Survey of Latin America and the Caribbean, the seventy-fifth issue, outlines the region’s economic performance in 2022 and analyses trends in the early months of 2023, as well as the outlook for growth for the year and for 2024. It highlights the external and domestic factors that have influenced the region’s economic performance and how these factors will affect economic growth in the coming years. Part II of this edition analyses the macroeconomic repercussions of climate change on the economies of Latin America and the Caribbean and the potential financial mechanisms for facilitating the investment needed to make economies resilient and drive dynamic, sustained and sustainable growth. The estimations presented in chapter II suggest that owing to the intensification of climate shocks, by 2050, the gross domestic product (GDP) of six countries of the region that are highly exposed to climate change risks could be between 9% and 12% lower than under a business-as-usual growth scenario. Fully offsetting these economic losses would require an exceptionally large additional investment effort, of between 5.3% of GDP and 10.9% of GDP per year. In view of the magnitude of this investment effort, chapter III posits the need for a framework with multiple sources of financing to ensure greater mobilization of domestic and external resources. Chapter IV explores the role that central banks and financial supervisors can play in addressing climate risks and strengthening sustainable financing and investment. The report also notes that decisive action is needed to align the requisite financial flows with national climate goals, by expanding the financing mechanisms available for financial intermediation, adjusting the management of central banks’ asset portfolios to make them sustainable and supporting initiatives that foster the development of sustainable capital markets.